(untitled) (Journal of the College of Basic Education, 2024)
Unjust coercion is considered an injustice that God Almighty has forbidden, as He forbids assaulting the rights of His servants and prohibits everything that leads to conflict and severance between them. He makes the basis of contracts consent and choice, including marriage contracts, divorce contracts, and taking them back. I have chosen in this research to explain The effect of coercion on taking back, which is one of the legislations of the divorce system in Islam, and explaining the opinions of jurists regarding its occurrence or non-occurrence under coercion, knowing their evidence and discussing it, and stating the most likely opinion on the issue.